Impact of Different Sources of Nutrients on Growth and Yield Attributes of Groundnut (Arachis hypogaea L.) - Chaudhri, Rajesh; Choudhary, Roshan; Choudhary, R. S. (International Journal of Bio-resource and Stress Management, 2023)
Field experiment was conducted during kharif seasons of 2011 and 2012 at S.K.N. College of Agriculture, Jobner to study the effect of integrated nutrient management levels on growth parameters and yield of groundnut (Arachis hypogaea L.). Treatments consisted of the eight levels of organic manures and fertilizers in main plots [control, RDF (25 kg N+45 kg P2O5 kg ha-1), FYM 15 t ha-1, FYM 7.5 t ha-1+½ RDF, poultry manure 6 t ha-1, poultry manure 3 t ha-1+½ RDF, vermicompost 5 t ha-1, and vermicompost 2.5 t ha-1+½ RDF] and four levels of iron in sub plots [0.0, 5.0, 10.0 and 15.0 kg ha-1] were compared. Poultry manure 3 t+½ RDF produced significant higher dry matter accumulation (65 g plant-1), branches plant-1 (20.45), dry weight of nodules (109 g), leaf area index (5.62), no.of pods plant-1 (24.37), no. of kernels pod-1 (1.88), pod yield (2863 kg ha-1) and stover yield (4365 kg ha-1) of groundnut at harvest over rest of the treatments during both the years of study. Iron levels up to 10 kg ha-1 also significantly increased the dry matter accumulation (59.8 g plant-1), branches plant-1 (19.08), dry weight of nodules (104.9 g), leaf area index (5.74), no. of pods plant-1 (21.30), no. of kernels pod-1 (1.61), pod yield (2461 kg ha-1) and stover yield (3868 kg ha-1) of groundnut over control and 5.0 kg Fe ha-1 but was found at par with 15 kg Fe -1 during both the years of study on pooled basis. However, poultry manure 3 t+½ RDF proved significantly superior over other treatments in respect growth and yield attributes of groundnut.